The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1016/j.ijrobp.2008.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organ Motion on Conformal vs. Intensity-Modulated Pelvic Radiotherapy for Prostate Cancer

Abstract: Purpose: To compare an intensity-modulated radiotherapy (IMRT) planning approach for prostate pelvic RT with a conformal RT (CRT) approach taking into account the influence of organ-at-risk (OAR) motion. Methods and Materials: A total of 20 male patients, each with one planning computed tomography scan and five to eight treatment computed tomography scans, were used for simulation of IMRT and CRT for delivery of a prescribed dose of 50 Gy to the prostate, seminal vesicles, and pelvic lymph nodes. Planning was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
16
1
Order By: Relevance
“…In a comparable study by Hysing et al on prostate cancer where the target also included the regional lymph nodes, the gEUD using IMRT was 40 Gy and 46 Gy for the bowel and rectum, respectively [13]. The difference in gEUD between our study and the study by Hysing et al reflects the different volumes of normal tissue included in the PTV for prostate and bladder RT, respectively.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…In a comparable study by Hysing et al on prostate cancer where the target also included the regional lymph nodes, the gEUD using IMRT was 40 Gy and 46 Gy for the bowel and rectum, respectively [13]. The difference in gEUD between our study and the study by Hysing et al reflects the different volumes of normal tissue included in the PTV for prostate and bladder RT, respectively.…”
Section: Discussioncontrasting
confidence: 43%
“…However, it is well known that the ORs, and especially the bowel will change position between treatment fractions [26]. In the study by Hysing et al, the IMRT sparing of the bowel and rectum persisted when the intra-fractional movements were analyzed on repeated CT scans [13]. Because of limited accuracy and definition of the targets and ORs, comparison with other studies is difficult, and the correlation between gEUD and clinical outcome may be problematic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it has been pointed out, that over the past decade intensity-modulated radiation therapy (IMRT) has shown its superiority to three-dimensional conformal radiotherapy (3DCRT) in the treatment of prostate cancer, producing more conformal dose distributions for the target volume with minimal longterm toxicities in the organs at risk (OAR) [7,12,15]. Thereby image guidance is recommended to reduce errors of patient setup and internal motion of the prostate [12,19,24,25].Different algorithms for the optimisation have been described.…”
Section: Background and Purposementioning
confidence: 99%
“…Large amplitude motion and deformations of the bowel have been observed [7][8][9][10]. It has been reported that only a minor part (i.e.…”
Section: Introductionmentioning
confidence: 99%